The Effects of Organizational and Political Factors on the Development of Performance Measurement System (PMS) of Local Government Institutions - Parwoto Parwoto; Abdul Halim (Universitas Muhammadiyah Yogyakarta, Indonesia, 2020)
Research aims: This study aims to examine the influence of organizational and political factors on the development of performance measurement systems (PMS) based on its development purpose and identify the phenomenon of institutional isomorphism.Design/Methodology/Approach: This research uses mixed methods with sequential explanatory strategies. Quantitative data were obtained by survey using questionnaires and qualitative data collection using semi-structured interviews. Quantitative data analysis uses SEM PLS, and qualitative data analysis uses Content Analysis (CA).Research findings: This research shows that the open attitude of the local government apparatus in accepting change, strong commitment from the leaders, broad enough authority for management, and strong political support from internal and external determine the success of the PMS development process in local government institutions. Furthermore, the phenomenon of institutional isomorphism is also still found in the PMS development process in local government institutions.Theoretical Contribution/ Originality: This study complements previous research on the factors that influence the development of PMS and adds evidence that the phenomenon of institutional isomorphism exists in the PMS development process. Research in this field has not been much researched in public sector accounting, particularly in Indonesia.Practitioner/Policy implication: This research provides input to the local government regarding the factors that need to be considered in the PMS development process, so that the PMS development policy is successful and can improve the performance of the local government.Research limitation/Implication: The minimum number of respondents who are willing to be interviewed and the research sample is only limited in the DIY region is a limitation in this study that might affect the results. Further research is recommended to continue using the mixed methods by expanding the distribution area of the sample used and adding other variables that are considered influential and able to capture the phenomenon of institutional isomorphism in the PMS development process.